A Spatial Patterns Identification Method of Rural Residential Land Change Integrating Dynamic and Multi-Scale Information - Jiang, Guanghui; Chen, Tianqian; Zhang, Ruijuan; Tian, Yaya; Wu, Siduo (Frontiers in Environmental Science, 2022)
Affected by rapid urbanization, the spatial layout of rural residential land (RRL) is facing urgent reconstruction and adjustment. The study of spatial change patterns of RRL can provide a basis for optimization and adjustment. We chose the Pinggu of Beijing as the study area. Taking into account the layout characteristics of RRL from 2005 to 2015, a combination matrix method was used to identify the spatial change patterns. The distribution characteristics of the change patterns under different environmental gradients were further analyzed. The study shows that the layout types of RRL in Pinggu in 2015 were dominated by the dispersion-regular-large scale (DRL) cluster type and concentration-regular-large scale (CRL) cluster type. The area of RRL patches in Pinggu increased by 686.89 hm2 from 2005 to 2015, which was approximately 12%. The main spatial change patterns of the RRL are the cluster leapfrog dispersion change pattern and cluster edge-expansion concentration change pattern. The influence of topography and location on RRL shows a relatively obvious vertically decreasing pattern. The spatial patterns of RRL use are changing at an accelerated rate due to the advanced production environment represented. Our study analyzes the changing pattern of RRL from multiple environmental gradients and provides a basis for the formulation of RRL layout optimization strategies.